Blindness caused by an ischemic optic neuropathy by spontaneous carotid dissection. Report of a case - Miranda, Marcelo; Venegas, Pablo; Kagi, Marianne (Revista medíca de Chile, 2003)
In young and middle age subjects, spontaneous carotid dissection is an increasingly recognized cause of ischemic stroke. Their usual presentation is facial pain with a Horner syndrome and a contra lateral paresis. Blindness has been reported as a presenting symptom in only a few cases. We report a 50 years old man who presented with amblyopia in the left eye, without periocular pain. Fundoscopy showed papilledema and a peripapillar hemorrhage, compatible with an ischemic optic neuropathy. A magnetic resonance angiography confirmed a left carotid dissection.